IMPROVE STUDENTS' WRITING SKILLS FOR ENGLISH MAJOR STUDENTS - Sarah Hendratno; Ameera Fadhillah; Ayu Lestari; Jumita simbolon; Mandyansyah Suhendra; Priska Oktaviani; Tiarnita Maria Sarjani Br. Siregar (Ravine Publisher, 2023)
Writing is considered the most challenging skill for language learners because they need a certain amount of L2 background knowledge about the rhetorical organization, the proper use of language, or the specific lexicon they want to convey to their readers. It is not uncommon for students who are English majors to find it challenging to hone this writing skill. This study aims to see the extent of students' writing skills in the English department and to provide some ways to improve their writing skills. The method used in this study is a qualitative research method with observations of students majoring in English. The results of the research found that students majoring in English who were tested showed that students’ writing skills are still inferior and have many mistakes. This research is intended for readers to see a good writing strategy to improve the writing skills of English majors. It can be enhanced with techniques for better writing skills, such as brainstorming before starting and asking WH questions.